Living with cancer: from the diagnosis to the treatment - Delma Riane Rebouças Batista; Magda de Mattos; Samara Frizzeira da Silva (Universidade Federal de Santa Maria, 2015)
Aim: to describe the difficulties faced by cancer patients, from diagnosis to treatment. Method: descriptive and exploratory research with, a qualitative approach, developed with six people diagnosed with cancer, in both genders. The data was carried out through individual semi-structured interviews between February and July 2014. In interpreting the data, we used the content analysis. Results: two categories emerged: "the difficulties in discovering the disease" and "difficulties in the treatment of cancer." It is evident that the difficulties faced by cancer patients are influenced by the delay in diagnosis, difficulties in access to tests, side effects and barriers to completion of the treatment. Conclusion: the results confirm the need for continuing education in service of the professionals working in the health care network. Knowing how is the process of illness and treatment of cancer patients can improve the service conditions of the multidisciplinary team